PENGARUH RETURN ON ASSET, LEVERAGE, UKURAN PERUSAHAAN DAN KONEKSI POLITIK TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2012-2015) - Annisa '; Taufeni Taufik; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to find out the effect of return on assets, leverage, firm size, and political connections on the extent of tax avoidance with proxy cash effective tax rate. Independent variables used in this study are return on assets, leverage, firm size, and political connections while the dependent variable in this study is tax avoidance are measured using Cash Effective Tax Rate (CETR). The population in this study is the the manufactured company on the Indonesian Stock Exchange in 2012-2015. The sample was determined by the purposive sampling method and obtain 40 companies. Type of data used was secondary data obtained from www.idx.co.id or corporate websites. Data analysis conducted with multiple regression model with help of software SPSS version 22,0. Of the result of the testing that has been done, that return on assets has significant value and a negative effect on tax avoidance. Leverage has significant value and a positive effect on tax avoidance. Meanwhile firm size and political connections have no significant effect on tax avoidance. Based on total adjusted R-square result proved that variables of return on assets, leverage, firm size, and political connections effect on tax avoidance results of 17,9% while the rest of 82,1% were affected by other variables that were not performed in this study like Independent commissioner board, audit committee and executive characteristics.Keywords: Return On Assets, Leverage, Firm Size, Political Connections, Tax Avoidance